O impacto da covid-19 nas periferias: uma análise espacial a partir dos casos e óbitos no Rio de Janeiro - Heitor Soares Farias; Gustavo Mota de Sousa; André Santos da Rocha; Leandro Dias de Oliveira (Confins)
After almost a year, the covid-19 pandemic did not prove to be as democratic as was announced: the urban peripheries, more socially vulnerable, proved to be privileged areas of contamination. Thus, the objective of this article is to analyze the impacts of the covid-19 in the peripheries of the Metropolitan Region of Rio de Janeiro, highlighting the capital and the municipalities that make up the Baixada Fluminense. Presenting a conceptual debate on social vulnerability and dialoguing with the field of public health, maps and tables were produced, based on official case and death data from the State of Rio de Janeiro Health Department, by municipality, and estimated population in 2020, from IBGE Cidades, to calculate the Prevalence, Mortality and Lethality Rates, to seek an analytical understanding of the diffusion of covid-19 in the peripheral territories of Rio de Janeiro. Despite the obstacles to underreporting, the results made it possible to identify a similar spatial behavior between groups of municipalities, highlighting the importance of social vulnerability as one of the most relevant elements of the spread of covid-19.